Investigating the language, cognition and self-monitoring abilities of speakers with jargon output. Issue 9 (2nd September 2019) - Purcell, Rachel; Lambon Ralph, Matthew A.; Sage, Karen
ABSTRACT: Background : Jargon aphasia is a complex acquired language disorder which is characterised by fluent verbal output and usually accompanied by poor error monitoring. Written or graphemic jargon may or may not co-occur with spoken jargon. Intervention to address jargon behaviour is difficult to design due to the presence of poor self-monitoring of errors. Aims : This study investigated the potential underpinning language and cognitive systems in the production of jargon behaviour and the ability to monitor spoken errors. We propose that jargon behaviour – poor language monitoring and jargon output – arise from an intersection of impaired language and cognitive systems. Methods & Procedures : Six individuals with jargon aphasia participated in the study. A range of background language and cognition tests were selected. Experimental tests were designed to measure participants' abilities to monitor their spoken and written output. Outcomes & Results : Only three of the six participants were able to complete the full assessment battery, with each participant demonstrating a different profile of results across the experimental language monitoring tests. Participants who were better at monitoring their speech (AJ, AE, and LS) scored on the higher end of tests on access to auditory discrimination and repetition. Results from the background cognitive tests identified a range of cognitive impairments including difficulties with attention, problem solving, and sequencing. Conclusions : Participants with relatively well-preserved skills in auditory discrimination and repetition were better at monitoring their spoken output. This suggests that language competence has a contribution to self-monitoring. All participants were found to have previously unidentified significant cognitive deficits. The significance of this is discussed in relation to language monitoring skills and potential treatment approaches.